BEHAVIORAL APPROACH ON THE MEXICAN STOCK MARKET MODELED THROUGH PLS-SEM (Proceedings of the International Conference on Education, 2021)
Dataset does not exist anymore: Marine, F. J., Bribiesca, J. C., & Arrona-Palacios, A. (2021, October). BEHAVIORAL APPROACH ON THE MEXICAN STOCK MARKET MODELED THROUGH PLS-SEM. In Proceedings of the International Conference on Education (Vol. 7, No. 1, pp. 220-232).The dataset with the identifier https://doi.org/10.17501/24246700.2021.7121 was withdrawn.
Keywords: Investor behavior; risk; market efficiency; Structural Equations; partial Least Squares methods